College students attitude and mathematics achievement using web based homework - Leong, K.E.; Alexander, N. (Eurasia, 2014)
The goal of this study was to understand how students` attitudes were connected to their mathematics learning and achievement. This investigation of students (n = 78) and their attitudes was specific to web-based homework in developmental mathematics courses in a two-year community college located in a large urban city in the United States. A mixed-methods investigation was utilized to analyze the relationships between students` attitudes and their mathematics achievement. The qualitative findings from the survey questionnaire show mixed responses from participants on the benefits and disadvantages of a web-based homework platform. Additionally, quantitative results, represented through cluster analysis, show the relationship between three groups of students, their attitudes and their mathematics achievement. The results of this study suggest that students with lower and average mathematics achievement hold more positive attitudes toward using a web-based homework platform compared to higher achieving students. Based on these results, it can be noted that web-based homework platforms serve an important role in student learning and attitudes toward mathematics in developmental courses, likely because the immediate feedback given helps to improve student understanding.